Pain Relief during Oocyte Retrieval by Transcutaneous Electrical Acupoint Stimulation: A Single-Blinded, Randomized, Controlled Multicenter Trial - Zhou, Liying; Yang, Shuo; Bu, Yifan; Lan, Yonglian; Han, Songping; Han, Ji Sheng; Sun, Wei; Zhang, Xiaoyu; Fan, Yuan; Kong, Rui; Li, Rong; Wang, Shuyu; et al. (Evidence-based complementary and alternative medicine, 2020)
Acupuncture has pain-relief effects, but no data were available on the use of transcutaneous electric acupoint stimulation (TEAS) in pain relief during oocyte retrieval. This study was designed to examine the effect of TEAS for pain relief in women undergoing transvaginal ultrasound-guided oocyte aspiration. This single-blinded, multicenter, randomized controlled trial was performed in China between May 2013 and May 2015. The subjects were randomized to mock TEAS and TEAS. TEAS or mock TEAS was administered 30 min before oocyte retrieval until the end of the operation. The primary and secondary endpoints were the pain measured using the visual analog scale (VAS) within 1 min and 1 hour after oocyte retrieval, respectively. Serum β-endorphin levels were tested in the first 50 patients/group. 390 women were undergoing oocyte retrieval. Pain levels evaluated using VAS within 1 min (18.6 ± 1.3 vs. 24.4 ± 1.7, P<0.01) and 1 h after oocyte aspiration (4.6 ± 0.7 vs. 6.8 ± 0.8, P<0.05) were lower in the TEAS group than in the mock TEAS group. Nausea assessment revealed a significantly lower VAS score in the TEAS group within 1 min (1.2 ± 0.4 vs. 2.9 ± 0.7, P<0.033). Serum β-endorphin levels were significantly higher in the TEAS group than in the mock TEAS group (11.4 ± 0.5 vs. 9.1 ± 0.4, P<0.001) after retrieval. Serum β-endorphin levels were higher in the TEAS group after the procedure than baseline (11.4 ± 0.5 vs. 9.1 ± 0.3, P<0.001). Oocyte retrieval causes pain and discomfort, but TEAS is effective and safe for suppressing the pain and alleviating nausea associated with the operation.